Behavioural activation induced in the rat by substance P infusion into ventral tegmental area: implication of dopaminergic A10 neurones. - Kelley, A; Stinus, L; Iversen, S (1979)
The functional role of the putative transmitter substance P (SP) was studied using a behavioural approach. SP infusion into the ventral tegmental area in awake rats elicited an increase in locomotor activity which could be blocked by either infusion of a neuroleptic into the nucleus accumbens septi (NAS) or by 6-hydroxydopamine (6-OHDA) lesions of the ascending dopaminergic A10 neurones. Our results suggest that SP induces its behavioural effects through activation of dopaminergic A10 neurones, and imply that endogenous SP may have an important modulatory role.